2003
DOI: 10.1046/j.1523-1739.2003.01458.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Urbanization and Habitat Fragmentation on Bobcats and Coyotes in Southern California

Abstract: Urbanization and habitat fragmentation are major threats to wildlife populations, especially mammalian carnivores. We studied the ecology and behavior of bobcats (   Lynx rufus ) and coyotes ( Canis latrans ) relative to development in a fragmented landscape in southern California from 1996 to 2000. We captured and radiocollared 50 bobcats and 86 coyotes, determined home ranges for 35 bobcats and 40 coyotes, and measured their exposure to development (  “urban association”  ) as the percentage of each home ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
357
3
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(408 citation statements)
references
References 35 publications
32
357
3
10
Order By: Relevance
“…Ultimately, it is at the local level where social and ecological impacts of urbanization of rural lands may be greatest (see Stein et al, 2007 for examples of some local implications of residential development). Additionally, the spatial arrangement of rural lands that are converted to developed uses, even for small areas, may magnify the ecological impacts from urbanization (e.g., wildlife habitat use; Dixon et al, 2006;Johnson and Collinge, 2004;Ng et al, 2004;Riley et al, 2003).…”
Section: Conversion Of Undeveloped Landsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, it is at the local level where social and ecological impacts of urbanization of rural lands may be greatest (see Stein et al, 2007 for examples of some local implications of residential development). Additionally, the spatial arrangement of rural lands that are converted to developed uses, even for small areas, may magnify the ecological impacts from urbanization (e.g., wildlife habitat use; Dixon et al, 2006;Johnson and Collinge, 2004;Ng et al, 2004;Riley et al, 2003).…”
Section: Conversion Of Undeveloped Landsmentioning
confidence: 99%
“…During this time, approximately 680,000 ha of rural land were converted to developed uses annually (USDA NRCS, 2007). Net loss and fragmentation of rural lands have many potential implications for the goods, services, and functions of natural resources provided by such landscapes (e.g., Alberti et al, 2003;Arnold and Gibbons, 1996;Collins et al, 2000), the species that use them and their habitat (e.g., Faeth et al, 2005;McKinney, 2002;Riley et al, 2003), and the ability of invasive species to establish themselves (e.g., Holway, 2005;Lambropoulos et al, 1999;Yates et al, 2004). Past research also has suggested that the addition of homes and other structures into rural landscapes can increase the probability of wildland fire and complicate fire management efforts (e.g., Berry and Hesseln, 2004;Cardille et al, 2001;Gebert et al, 2007;Sturtevant and Cleland, 2007), can have deleterious effects on water quality (Atasoy et al, 2006;Pijanowski et al, 2002b;Tang et al, 2005), and possibly can reduce the propensity for forest management and timber harvest Munn et al, 2002;Wear et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known as to how raccoons exploit the urban matrix outside urban parks. Other mesocarnivores (e.g., coyotes [Canis latrans]) exhibit a positive relationship between home range size and the proportion of the home range that spans urbanized land (Riley et al 2003;Gehrt et al 2009), suggesting a cost to living in an urban landscape. However, if raccoon home range size does not increase with urbanization, this would suggest they are synanthropic (Gliwicz et al 1994) and capable of effectively exploiting various parts of the urban landscape.…”
Section: Introductionmentioning
confidence: 99%
“…It has severe long-term consequences for wildlife, including reduction of richness, survival and reproduction of native species (Hansen et al, 2005). The proximate causes are habitat loss and fragmentation (Kluza et al, 2000;Riley et al, 2003Riley et al, , 2005, species introductions (Riley et al, 2005;Olden et al, 2006), alteration of ecological processes (e.g. changes of fire regimes and nutrient cycles) (Hansen et al, 2005), and direct antropogenic disturbances models are proving to be very useful tool for studying humanwildlife conflicts and providing insights into more effective forms of wildlife management (Bennett et al, 2009).…”
Section: Introductionmentioning
confidence: 99%